(untitled) - Becklin, Karonne J. (Boston, 2006)
This sixth edition of Medical Office Procedures, a well-known and widely used textbook, provides the required background for the responsibilities of the administrative medical assistant. To prepare students for the greatly increased importance on the computerization of routine task and of communications. This textbook allows for the integrated application of office procedures skills and knowledge in the classroom through the use of simulation techniques
Keywords: Medical assistants,Medical offices,Phụ tá y tế,Cơ quan y tế; Management,Quản lý